Fur seal arbitration [electronic resource] : argument of the United States before the Tribunal of Arbitration convened at Paris under the provisions of the treaty between the United States of America and Great Britain, concluded February 29, 1892. (Washington, D.C. : G.P.O., 1893)
Electronic reproduction. Mode of access: Internet. 44